A Morphological Analysis of Derivational Affixes in Short Story ”The Ones Who Walk Away From Omelas” by Ursula K. Leguin 1973 - Shandra, Adinda Ayu; Zaim, M. (English Language and Literature, 2024)
This study aimed identify and examine the derivational affixes present in the short story "The Ones Who Walk Away From Omelas" by Ursula K. Le Guin (1973). The types of derivational affixes and how derivational affixes utilized in short story of "The Ones Who Walk Away From Omelas by Ursula K.Leguin. This research used descriptive qualitative study in which the data of this study was taken from the short story of "The Ones Who Walk Away From Omelas" by Ursula K.Leguin. In analyzing the short story, the researcher used (Lieber:2009) theory to identifying the types of derivational affixes and used (Yule:2010) to utilizing derivational affixes. . There are 76 derivational affixes found in the short story. There are 43 class changing suffix, 1 class maintaining prefix and 28 class maintaining suffix. In the short story "The Ones Who Walk Away from Omelas," several derivational affixes are prominently found, enriching the narrative with layers of meaning and enhancing the reader's engagement. Some of the most frequently observed derivational affixes include; -ness, -ing, -ful, -er, -ed, -ly, and -ous.